1984
DOI: 10.1128/jvi.49.3.686-691.1984
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of RNA primer removal by the RNase H activity of avian myeloblastosis virus reverse transcriptase

Abstract: The single-stranded DNA containing the Moloney murine leukemia virus origin for plus-strand synthesis was cloned in M13mp2 and used as a template for avian myeloblastosis virus reverse transcriptase in the presence of Moloney RNA which had been treated with pancreatic RNase A. The RNA pieces containing the polypurine stretch near the plus-strand origin were processed, presumably by RNase H, to generate primers for DNA synthesis which initiated both at the correct origin site and at one nucleotide downstream fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…Note that this proposition does not preclude RNAs from being used as primers after first strand DNA synthesis. Evidence conclusively shows that second strand DNA synthesis is initiated from a unique RNA primer termed the 'polypurine tract' (8)(9)(10)(11)(12)(13)(14) and perhaps from other RNAs (29). The results shown here and those ofothers (10,22,28) suggest that the use ofRNAs as primers is likely inefficient.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Note that this proposition does not preclude RNAs from being used as primers after first strand DNA synthesis. Evidence conclusively shows that second strand DNA synthesis is initiated from a unique RNA primer termed the 'polypurine tract' (8)(9)(10)(11)(12)(13)(14) and perhaps from other RNAs (29). The results shown here and those ofothers (10,22,28) suggest that the use ofRNAs as primers is likely inefficient.…”
Section: Discussionmentioning
confidence: 61%
“…The RNase H activity of the RT is proposed to be required at several stages of viral genomic replication. These include degradation ofthe RNA template after synthesis ofthe first strand of DNA (7), generation of a specific oligopurine ribonucleotide primer from which second strand DNA synthesis will initiate and subsequent removal of the oligopurine primer (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies demonstrated that initiation of plus-strand synthesis by the 3Ј PPT involves selective cleavage of viral RNA to produce the correct 3Ј end for subsequent extension by RT (13,24,47,48,53,62). The PPT primer is removed from plus-strand DNA by specific cleavages at or near the 5Ј terminus of the PPT and at the 3Ј RNA-DNA junction (5,24,46). Ultimately, the proper processing of the 3Ј PPT is of great importance since it precisely defines the left end of the linear DNA, which serves as a recognition and cleavage site for viral integrase (58).…”
mentioning
confidence: 99%
“…Omer and Faras (25) have shown that the avian myeloblastosis virus (AMV) RNase H can remove the tRNA primer from minus strong-stop DNA strands by a single cleavage at the junction between the RNA and the DNA chains. Similar studies with M-MuLV plus strands which had been synthesized in vitro and which retained an RNA primer revealed that the AMV RNase H removes the priming RNA fragment intact by cleaving at the junction between the RNA and the DNA (5). In both of these situations the basis for the recognition of the cleavage sequence may simply be the site at which the polynucleotide chain switches from ribonucleotides to deoxyribonucleotides.…”
Section: Dna-rna Hybrids Containing M-mulv Plus-strand Originmentioning
confidence: 87%